Influence. Work Environment, Work Discipline And Motivation Towards Employee Commitment To Serba Sambipitu Gunungkidul - Widhiatmoko, Wayan; Prayekti, Prayekti; Kirana, Kusuma Chandra (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
This study aims to determine the effect of the work environment, work discipline, and motivation simultaneously and partially on the commitment of the employeesoftheSambipituGunungkidul Department Store. The type of research used is quantitative. The population in this study were all employees at the department store with a total sample of 85 people. the type of data used is primary data. The aftereffects of this examination show that the workplace suffers a heart attack and critical impact on representative responsibility, work discipline suffers a heart attack and huge impact on worker responsibility, inspiration suffers a heart attack and huge impact on worker responsibility and work. environment, work discipline, and motivation have a significant effect together on commitment. Sambipitu Department store employees in Gunungkidul.